Role of solvent-anion charge transfer in oxidative degradation of battery electrolytes - Eric R. Fadel (Nature Portfolio, 2019)
Based on computations, the authors show that voltage stability of battery electrolytes is determined not by a single component but by formation of charge transfer complexes between salt anions and solvent molecules. A physical model is proposed and validated on several common electrolyte compositions.